Botulinum toxin for cerebral palsy; where are we now?. Issue 12 (19th November 2004) - Morton, R E; Hankinson, J; Nicholson, J
Abstract : In this article, the evidence base for botulinum-A treatment acquired in recent years is outlined, and the practicalities involved in providing this service are described. Botulinum-A is relatively new, and possible improvements for the future are considered.